2022
DOI: 10.1245/s10434-022-11805-9
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes After Cytoreductive Surgery with Hyperthermic Intraperitoneal Chemotherapy in Patients with Synchronous Versus Metachronous Onset of Peritoneal Metastases of Colorectal Carcinoma

Abstract: Background Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) is a treatment option for peritoneal metastases (PM) from colorectal carcinoma (CRC). Because of considerable morbidity, optimal patient selection is essential. This study was designed to determine the impact of the onset of PM (synchronous vs. metachronous) on survival outcomes after CRS-HIPEC. Methods Patients undergoing CRS-HIPEC for colorectal PM in two academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
0
15
1
Order By: Relevance
“…Nonetheless, the current literature is lacking a similar mucinous adenocarcinoma-specific study; the present study aims to fill this gap. In a recent study by Dietz et al [ 46 ], the survival outcomes after CRS + HIPEC in synchronous versus metachronous PM of CRC have been compared. Consistent with the available results, they found that synchronous PM patients presented with higher TN-stages ( p < 0.001) and that mucinous adenocarcinomas were more common in this group ( p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the current literature is lacking a similar mucinous adenocarcinoma-specific study; the present study aims to fill this gap. In a recent study by Dietz et al [ 46 ], the survival outcomes after CRS + HIPEC in synchronous versus metachronous PM of CRC have been compared. Consistent with the available results, they found that synchronous PM patients presented with higher TN-stages ( p < 0.001) and that mucinous adenocarcinomas were more common in this group ( p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the available results, they found that synchronous PM patients presented with higher TN-stages ( p < 0.001) and that mucinous adenocarcinomas were more common in this group ( p = 0.001). Furthermore, OS was significantly shorter for synchronous PM compared to metachronous PM patients (28 versus 33 months, respectively, p = 0.045) [ 46 ]. We can draw the same conclusion in this regard—that synchronous peritoneal metastatic disease demonstrates poor tumor characteristics and a more advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 6% of patients diagnosed with CRC have metastasis at the time of diagnosis. Of these patients, approximately 8% will have synchronous peritoneal involvement, while 20% will have liver metastasis [ 6 , 7 , 8 , 18 ]. The actual incidence of metachronous CRC metastasis is unknown but is estimated to be less than 10% based on a series.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of PCI values demonstrated that patients with the presence of SPM had a higher PCI (>20) (57 patients, 43.1%), while those with MPM had intermediate PCI values (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) (46 patients, 42.5%) (p = 0.014).…”
Section: Patient and Tumor Characteristics Categorized By Spm/mpm Tim...mentioning
confidence: 99%
See 1 more Smart Citation